Graphical User Interface Features In Building Attractive And Successful Websites - Abdo, Ahmed Mahdee; Alali, Sardar Hasan (European Scientific Journal, ESJ, 2016)
The process involve in building a successful website goes beyond knowing web developing languages such as HTML and CSS. The success or failure of any website depends heavily on the use of some aspects of Graphical User Interface. These aspects are usually reserved for client’s wishes and desires. The content features of the GUI are used to stay in touch with visitors. Therefore, this article will highlight some important GUI features used in building an attractive and a successful website.